2020
DOI: 10.3390/pr9010038
|View full text |Cite
|
Sign up to set email alerts
|

Ideal Feedstock and Fermentation Process Improvements for the Production of Lignocellulolytic Enzymes

Abstract: The usage of lignocellulosic biomass in energy production for biofuels and other value-added products can extensively decrease the carbon footprint of current and future energy sectors. However, the infrastructure in the processing of lignocellulosic biomass is not well-established as compared to the fossil fuel industry. One of the bottlenecks is the production of the lignocellulolytic enzymes. These enzymes are produced by different fungal and bacterial species for degradation of the lignocellulosic biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 149 publications
0
15
0
Order By: Relevance
“…Researchers have shown that characterization of cellulase producing bacteria and their genome functional analyses help to improve waste management [276]. All the wastes are now wisely used to manufacture useful goods such as enzymes, carbohydrates, biofuels, chemicals, low-cost energy fermentation streams, enhanced cattle diets, and human nutrition dietary supplements [204,277,278].…”
Section: Cellulase In Waste Managementmentioning
confidence: 99%
“…Researchers have shown that characterization of cellulase producing bacteria and their genome functional analyses help to improve waste management [276]. All the wastes are now wisely used to manufacture useful goods such as enzymes, carbohydrates, biofuels, chemicals, low-cost energy fermentation streams, enhanced cattle diets, and human nutrition dietary supplements [204,277,278].…”
Section: Cellulase In Waste Managementmentioning
confidence: 99%
“…Long or too short a fermentation time is not conducive to highlighting the nutritional value of fermented feed. It may even undermine its existence, making animal production disadvantageous (Iram, et al, 2021). Some studies have shown that as the fermentation time changes, the crude protein content, as well as small peptides and free amino acids (Bratosin, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the breakdown of such materials as an energy source is naturally more difficult than starch or simple sugars. The enzymes required for the breakdown are known as cellulases, hemicellulases, and lignases or lignin-modifying enzymes [11,12]. These enzymes are currently a major topic of research interest due to their underlying applications in the production of 2G biofuels [11].…”
Section: Introductionmentioning
confidence: 99%
“…The enzymes required for the breakdown are known as cellulases, hemicellulases, and lignases or lignin-modifying enzymes [11,12]. These enzymes are currently a major topic of research interest due to their underlying applications in the production of 2G biofuels [11]. However, such enzymes are currently not of industrial standards, and, in addition, they are very expensive as high loading is required.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation